Self-centering mechanism and seismic response of steel tension-only concentrically braced beam-through frames. (April 2021) - Dong, Baiping; Chen, Yueshi; Wang, Wei
Abstract: Tension-only concentrically braced beam-through frames (TCBBFs) are a newly proposed structural system that has great potential in damage mitigation for seismic design of low-rise steel buildings. In TCBBFs, columns usually have cold-formed hollow structural section (HSS) and are connected to the flanges of H-shaped beams at each floor level as an easy main frame assembly, and tension-only braces are installed to the main frame to provide additional lateral stiffness. The braces also serve as the replaceable fuse elements that contain the self-centering and energy dissipation properties of the system. This paper investigates the self-centering mechanism, structural behavior, and seismic performance of TCBBFs through integrated analytical and experimental studies. Particularly, shaking table tests were conducted to investigate the seismic response of TCBBFs with tension-only braces designed with four different methods. The effects of yielding, prestress level, and design methods of the braces on structural response are evaluated. The experimental results show that TCBBFs are capable of archiving uniform story drift response with self-centering ability upon unloading. Due to the self-centering mechanism of the system, the tension-only braces can be easily replaced and the main frame can be reused after the shaking of major earthquakes.